Energy in the world economy : a statistical review of trends in output, trade, and consumption since 1925 - Darmstadter, Joel.; Teitelbaum, Perry D.; Polach, Jaroslav George; Resources for the Future (Baltimore : Published for Resources for the Future by the Johns Hopkins Press, 1971)
The quantitative aspects of long-term trends in energy consumptions, production and foreign trade.
Includes bibliographical references: p. 875-876.
sju 25/01/2019
Loans
Keywords: Power resources